Removal of methyl red from aqueous solution using dried water hyacinth (Eichhornia crassipes) - Noridah, Abdullah (2010)
Colouring effluent from industrial activities such as methyl red may affect environment and human health. Many methods have been used to decolourise such effluent including using low cost adsorbent. The objective of this study is to study the adsorption of methyl red from aqueous solution using dried water hyacinth. This study was focusing on the effect of decolourisation due to dosage of adsorbent, initial concentration of solution, pH, and the contact time. Adsorption isotherm was examined in this study and both the isotherms was found to be applicable in the case of dye adsorption using dried water hyacinth. The applicability of the pseudo first order and second order was also examined to conforms the adsorption kinetic. And it is fit well with pseudo second order. The effectiveness of the method was determined by measuring the percentage of removal the methyl red. It is found that the removal was directly proportional to the dosage and contact time. For the initial concentration the removal is inversely proportional and for the pH, it increase from pH 2-3 and decrease from pH 3-7. The higher percentage of removal is 88% and the optimum condition for this study was identified. For the dosage, 3.0 g is the optimum and 50 mg/L for initial concentration, pH 3 and 120 minutes for the contact time. As a conclusion dried water hyacinth can be used as a adsorbent to remove the methyl red.